Relationship Between Pathological Findings and Cholinesterase Activity and Nitric Oxide Levels in Cattle Infected Naturally by Eurytrema coelomaticum - Schwertz C.I. (2016)
© 2016 Elsevier Ltd.The aim of this study was to evaluate the role of butyrylcholinesterase (BChE) (in the serum and pancreas), acetylcholinesterase (AChE) (in the whole blood and pancreas) and nitric oxide (NO) (in the serum and pancreas) in cattle infected naturally by Eurytrema coelomaticum. Fifty-one cattle were studied, including 33 infected by E. coelomaticum and 18 uninfected animals. Significantly greater AChE activity was found in the pancreas of infected animals (P <0.01); however, these cattle had lower AChE activity in whole blood. BChE activity was greater in the sera of infected animals (P = 0.05), but was less in pancreatic samples. NO levels were significantly higher in the sera (P <0.05) and pancreas (P <0.001) of infected cattle compared with uninfected animals. A positive correlation was found between AChE activity in the pancreas and parasite load, but there was negative correlation between pancreatic BChE activity and parasitic load. Expression of AChE, BChE and NO is therefore linked to the inflammation caused by E. coelomaticum in cattle.